Corporate cash holdings in an emerging market: the case of India - Lampousis, Athanasios (2017)
This thesis contributes to the literature on corporate cash holdings. The aim of the thesis is to shed light on the precautionary and agency motives of Indian firms’ cash holdings in their transition to integrating with the world economy. Three elements of India’s capital market transitioning phase are empirically investigated with respect to firms’ cash holdings and related financial policies. The first chapter of the thesis is concerned with the increasing presence of foreign institutional investors in Indian capital markets. It investigates whether and how foreign institutional ownership restricts the ability of corporate insiders to derive private benefits from firms’ cash holdings. This work contributes to the literature which studies corporate governance advancements in emerging markets. The second chapter of the thesis examines Indian firms’ sources of funds conducive to cash holdings. It investigates to what extent firms issue outside finance in order to save proceeds as cash. This work contributes to the literature which studies firms’ liquidity management under uncertain financing conditions. The final chapter of the thesis examines India’s capital market institutions. It investigates whether and how deepening domestic capital markets can relieve firm-level financial constraints. This work contributes to the literature which studies firm investment and growth in the context of developing market institutions. Collectively, these chapters examine the evolution of firm-level outcomes, including cash holdings, investment and firm values in the context of an emerging economy undergoing significant changes in its institutional architecture.